Applied Demography in the 21st Century Selected Papers from the Biennial Conference on Applied Demography, San Antonio, Teas, Januara 7-9, 2007 - Murdock, Steve H.; Swanson, David A. (Springer Netherlands : Imprint: Springer, 2008)
This work provides selected, peer-reviewed papers from the Biennial Conference on Applied Demography held in San Antonio, Texas on January 7-9 and sponsored by the Institute for Demographic and Socioeconomic Research at The University of Texas at San Antonio. The work contains chapters on several major topical areas that are central to applied demography including works on data Use and measurement, including detailed analysis of the American Community Survey and Master Address File, population estimation and projection, applied demography and health, and surveys examples of applied demographic analysis in such diverse areas as urban planning, educational planning, church selection, and private-sector marketing. The work also contains a section on the process of educating applied demographers delineating the types of skills needed by the applied demographer and providing examples of a program designed to meet such needs. Finally, the work presents beginning and concluding chapters that succinctly delineate the current characteristics and state of applied demography and the challenges facing it in the coming decades. The work provides an excellent overview of the state of applied demography at the beginning of the 21st Century which should be of interest to all demographers and be appropriate for adoption for courses in a variety of disciplines including demography, sociology, economics, geography, planning, statistics and others.